2021
DOI: 10.1111/gbb.12776
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the paternally inherited gene Magel2 alters the development of separation‐induced vocalization and maternal behavior in mice

Abstract: The behavior of offspring results from the combined expression of maternal and paternal genes. Genomic imprinting silences some genes in a parent-of-origin specific manner, a process that, among all animals, occurs only in mammals. How genomic imprinting affects the behavior of mammalian offspring, however, remains poorly understood. Here, we studied how the loss of the paternally inherited gene Magel2 in mouse pups affects the emission of separation-induced ultrasonic vocalizations (USV). Using quantitative a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…We have demonstrated the existence of a substantial proportion of unretrieved Magel2 +/−p pups by their WT dams as well as a delayed latency to retrieve the rest of them under cool exposure. Deficit in maternal care of Magel2 +/−p has been reported recently to occur specifically at P8 but not P6 [ 57 ]. Whilst they used a different Magel2 mutant mouse model (Magel2 tm1Stw ) and a distinct experimental approach, the difference in age is also an important factor.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated the existence of a substantial proportion of unretrieved Magel2 +/−p pups by their WT dams as well as a delayed latency to retrieve the rest of them under cool exposure. Deficit in maternal care of Magel2 +/−p has been reported recently to occur specifically at P8 but not P6 [ 57 ]. Whilst they used a different Magel2 mutant mouse model (Magel2 tm1Stw ) and a distinct experimental approach, the difference in age is also an important factor.…”
Section: Discussionmentioning
confidence: 99%
“…An analogous affect on attention-getting is also seen in a mouse model for AS that have increased ultrasonic vocalisations (USVs), which are used to signal to their mothers and elicit care-giving [ 109 ]. Fascinatingly, a recent study of mice lacking the PWS gene Magel2 demonstrated the opposite phenotype; decreased USVs that led to reduced caregiving from the dam [ 110 ].…”
Section: Why Should Imprinted Genes Be Involved In Brain Function At ...mentioning
confidence: 99%
“…In particular, neonate Magel2 -KO mice show feeding defects due to an altered onset of suckling activity, leading to neonatal growth retardation and a high mortality rate (approx. 50%) ( Schaller et al, 2010 ); feeding defects are accompanied by low rates of separation-induced vocalizations and altered spectral features ( Bosque Ortiz et al, 2022 ). The surviving adult Magel2 -KO mice have been extensively investigated for alterations in sensory-motor, cognitive and social abilities.…”
Section: Introductionmentioning
confidence: 99%